Xeromphis nilotica Stem-Bark Extract Attenuates CCl4-Induced Hepatic Damage and Oxidative Stress in Albino Rats. - Hamza, Hajjgana; Yahaya Musa, Maryam; Waziri, Ali; Daja, Aliyu (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Xeromphis nilotica is used by traditional practitioners in North East Nigeria to treat or manage various ailment such as inflammations, pains and stomach disorders. This study aimed to evaluate the probable protective effect of Xeromphis nilotica stem-bark extract against CCl4 induced hepatic injury in albino rats. Thirty-six rats were randomly divided into six groups. Group 1 served as the control and received 0.5mL of 1% tween 80 orally and 3ml/kgbwt olive oil intraperitoneally. Groups 2, 3, 4,5&6 were injected with 3ml/kgbwt of carbon tetra chloride (CCl4) in olive oil intraperitoneally to induce oxidative stress and thereafter group 4,5 &6 were treated with 100, 200, 400 mg/kgbwt of the extracts respectively. Group 2 serves as toxic control, while group 3 was treated with 25mg/kgbwt silymarin as standard control. Liver marker enzymes ALT, AST, total protein and albumin were assessed and results obtained was extrapolated by performing histological analysis of the liver tissues. The study revealed that treatment of rats with CCl4 caused marked weight loss, induced liver damage through elevated marker enzymes as well as significant decrease in catalase activity. However, administration of graded doses of X. nilotica extract effectively ameliorated the deviation caused by oxidative stress induced liver damage. Pathological examination of the liver tissues also supported the biochemical findings. It was concluded that supplementation of X. nilotica extract was beneficial in modulating the alteration induced in liver and serum variables of rats under the effect of CCl4 induced oxidative stress.